Eine Methode zur Massen- und Dauerzucht der Feuerwanze, Pyrrhocoris apterus Linnaeus (Heteroptera: Pyrrhocoridae). - Schlagbauer, Albert (Contributions to Entomology = Beiträge zur Entomologie, 1966)
A method for the mass-breeding of red bugs (Pyrrhocoris apterus Linnaeus) on larvae of Tenebrio molitor and seed of Tilia cor data is described. No diapause interrupt the sequence of generations under longday conditions at temperatures of 25°C ( = 78°F) in the laboratory.